Perancangan Mesin Pemutar Gerabah Dengan Kekuatan Tumpuan Maksimal 10 kg - Sir Anderson; Yazmendra Rosa; Khairul Amri; Maimuzar Maimuzar; Hendra Hendra; Aqli Ridawansyah (Jurnal Teknik Mesin, 2023)
Pottery is an art craft made from clay which besides having a high use value also has a pretty good aesthetic value. Pottery craft business has existed in Indonesia since ancient times until now. This business has a deficiency in the production machine part, where the production machine still uses human power as the main driving force during the rotation during the pottery making process. Therefore, a modification of a better pottery turning machine is needed to support the pottery craft business. The design of this pottery turning machine uses a working drawing design of a pottery turning machine product with a rotating speed that can be adjusted according to work requirements via a speed control pedal. The pottery turning machine has a strong construction with machine specifications of length 760 x width 400 x height 700 mm, with the addition of 2 pulleys with a first pulley diameter of 2.5 inches, and a second pulley diameter of 12 inches with a connecting belt using type A-57. And by using umbrella gears with a ratio of z1 = 25 and z2 = 50 with a maximum pedestal capacity of 10 kg.